2017
DOI: 10.3389/fpls.2017.00520
|View full text |Cite
|
Sign up to set email alerts
|

Barcode System for Genetic Identification of Soybean [Glycine max (L.) Merrill] Cultivars Using InDel Markers Specific to Dense Variation Blocks

Abstract: For genetic identification of soybean [Glycine max (L.) Merrill] cultivars, insertions/deletions (InDel) markers have been preferred currently because they are easy to use, co-dominant and relatively abundant. Despite their biological importance, the investigation of InDels with proven quality and reproducibility has been limited. In this study, we described soybean barcode system approach based on InDel makers, each of which is specific to a dense variation block (dVB) with non-random recombination due to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Therefore, 202 dVB-specific insertion/deletion (indel) markers have been developed [33]. A barcode system was established, which clearly distinguishes 147 Korean soybean varieties and is regularly updated whenever new varieties are developed [34,35]. The development of DNA markers has been simplified due to the active progression of genome research, but the development of DNA markers through full-length genome analysis in a small-scale laboratory is still difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 202 dVB-specific insertion/deletion (indel) markers have been developed [33]. A barcode system was established, which clearly distinguishes 147 Korean soybean varieties and is regularly updated whenever new varieties are developed [34,35]. The development of DNA markers has been simplified due to the active progression of genome research, but the development of DNA markers through full-length genome analysis in a small-scale laboratory is still difficult.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, a wealth of polymorphism data can now be obtained from a massive amount of sequencing data using high-throughput sequencing technologies [ 49 ]. In addition, Sohn et al [ 38 ] reported that the InDel-based barcode system focuses on usability, and provided an efficient resource management system. In addition to the InDel-based barcode system, morphological descriptors are now emerging that aim to identify tartary buckwheat accessions, which can be used to verify key genomic factors that explain or predict major agronomic traits.…”
Section: Introductionmentioning
confidence: 99%
“…SNPs, as well as InDels, were discovered in ndhA and clpP genes at the level of Pyrus species and cultivars. Recently, InDel markers in cp have been used for genetic identification in many crops such as potato, quinoa, ginseng, onion, and soybean (Hong 1 Niitaka TCC CAA AGTTC ----TTT TTT TTT TCA AAT AAA AAAA ---------TTT TAT TTT CAT ATT CTT 2 Whangkeumbae TCC CAA AGTTC ----TTT TTT TTT TCA AAT AAA AAAA ---------TTT TAT TTT CAT ATT CTT 3 Amanogawa TCC CAA AGTTC ----TTT TTT TTT TCA AAT AAA AAAA ---------TTT TAT TTT CAT ATT CTT 4 Gamro TCC CAA AGTTC ----TTT TTT TTT TCA AAT AAA AAAA ---------TTT TAT TTT CAT ATT CTT 5 Sunwhang TCC CAA Joh et al 2017;Lee et al 2017;Sohn et al 2017;Cho et al 2016). It is easy and inexpensive to use (Qiao et al 2016).…”
Section: Discussionmentioning
confidence: 99%